Uma leitura sobre a geografia escolar de Hilton Sette Correia - Costa, Leila Barbosa (2010)
The dissertation is a reading on the school Geography Hilton Sette and Manuel Correia de Andrade aims to discuss the teaching of geography from the first authors of textbooks and the Northeast Hilton Sette Manuel Correia de Andrade. These manuals were published in the 1950s, in a social and educational context in which it is thought new directions for education in Brazil. We began the first chapter of this work, defending the idea of school textbooks as historical documents, for both did research on work by leading scholars of the textbook issue and brought its main contributions. Even this first stage of the thesis, we emphasize the importance of textbooks to the understanding of school subjects. The reading marks, left by students who studied with school books Sette Hilton and Manuel Correia de Andrade were also significant for the study of the methodology applied by teachers in the period that the books were used. We also performed a thorough analysis in textbooks of other authors of geography, such as: Aroldo de Azevedo, Moses Gicovate, Renato Stempniewski in partnership with Eli Piccolo, and Geraldo Sampaio de Souza with Jose Armando Sampaio de Souza, published in the same time cutting it the textbooks on the Sette Hilton and Manuel Correia de Andrade. The second chapter on geography and school manuals Sette Hilton and Manuel Correia de Andrade, we propose a brief history of the discipline in which, on occasion, we treat the configuration of secondary education in Brazil during the 1950s. The scientific debates on contemporary textbooks Sette Hilton and Manuel Correia de Andrade, likewise, were part of the composition of this text. In the last chapter, discussing, specifically, the teaching of geography from the content of textbooks in the authors' study as well as school culture that involve education in the period in which the authors Sette Hilton and Manuel Correia de Andrade were in classroom teaching Geography in schools in the state of Pernambuco.